TEMBIKAR PRASEJARAH-PROTOSEJARAH DI KAWASAN PANTURA JAWA TENGAH: KAJIAN BAHAN BAKU BERDASARKAN ANALISIS PETROGRAFIS - Gunadi Kasnowihardjo (KALPATARU, 2017)
Pottery or often called gerabah is one of the results of technology that developed in the neolithic period, until now some people in Central Java in general and in the northern coast of Rembang regency in particular still found pottery craftsmen, one of them is in Balong Mulyo Village, Kragan District, Regency of Rembang. To get raw materials such as clay and sand, Balong Mulyo pottery craftsmen apparently make use of natural resources in their environment. As one artifact made from clay and sand materials, petrographically pottery can be analyzed type content and mineral percentage. The results of an analysis of petrographic samples of pottery fragments from prehistoric-protohistoric sites in the northern coast of Central Java such as Binangun, Leran, Plawangan and Tanjungan sites, have in common with the pottery samples from Balong Mulyo. This is one of the benefits of applying petrographic studies in archaeological research. In addition, the results of this petrographic study can provide an explanation that prehistoric-protohistoric humans in the northern coastal area of Central Java to meet their daily needs have utilized the natural resources of their environment, one of which is in pottery technology. Tembikar atau sering disebut gerabah adalah salah satu hasil teknologi yang berkembang pada masa neolitik, hingga sekarang sebagian masyarakat di Jawa Tengah umumnya dan di daerah pantai utara Kabupaten Rembang khususnya masih ditemukan pengrajin tembikar, salah satu di antaranya adalah di Desa Balong Mulyo, Kecamatan Kragan, Kabupaten Rembang. Untuk mendapatkan bahan baku seperti tanah liat dan pasir, para pengrajin tembikar Balong Mulyo rupa-rupanya memanfaatkan sumberdaya alam di lingkungan mereka. Sebagai salah satu artefak yang dibuat dari bahan baku tanah liat dan pasir, secara petrografis tembikar dapat dianalisis kandungan jenis dan prosentasi mineralnya. Hasil analisis petrografi sampel fragmen tembikar dari situs-situs prasejarah-protosejarah di kawasan pantai utara Jawa Tengah seperti Situs Binangun, Leran, Plawangan, dan Tanjungan, secara garis besar memiliki kesamaan dengan sampel tembikar dari Balong Mulyo. Inilah salah satu manfaat penerapan kajian petrografi dalam penelitian arkeologi. Selain itu, hasil kajian petrografi ini dapat memberikan penjelasan bahwa manusia prasejarah-protosejarah di kawasan pantai utara Jawa Tengah untuk memenuhi kebutuhan hidup sehari-hari mereka telah memanfaatkan sumberdaya alam lingkungannya, salah satu di antaranya adalah dalam teknologi pembuatan tembikar.